Response of sheep to supplementation of Probio-catalytic in the diets - Haryanto, B; ., Supriyati; Jarmani, S.N (Indonesian Animal Sciences Society, 2008)
biotic and catalytic supplement, on the productive performances of sheep fed Pennisetum purpuphoides (King grass). The concentrate was made of rice bran, molasses-coated palm kernel cake, minerals and salt. Probio-catalytic supplements were added either at 0.5% or 1.0% of the concentrate. The probiotic in the probio-catalytic supplements was either Probion (produced by Balitnak) and assigned as probio-catalytic supplement A, or a mixture of rumen microbes of buffaloes which was assigned as probio-catalytic B. The catalytic supplement consisted of gelatinized sago, Zn, Co, urea and sulfur. Twenty heads of male young sheep with an average liveweight of 18.8 Â± 1.7 kg were divided into 4 groups based on the bodyweight and allocated to 5 feeding treatments. The treatments were (1) Control (without probio-catalytic supplement), (2) R1 addition of probio-catalytic supplement A at 0.5%, (3) R2 addition of probio-catalytic supplement A at 1.0%, (4) R3 addition of probio-catalytic supplement B at 0.5%, and (5) R4 addition of probio-catalytic supplement B at 1.0%. The experiment was carried out by a randomized block design. A four-week adaptation period was then followed by a 12-week feed intake data collection and growth trial. An intake and digestibility study of the feed was carried out for 7 days. Rumen fluids were taken for analysis of pH, ammonia and volatile fatty acids and microbial population. Results indicated a significantly greater weight gain in the group received R1 than that of the other treatments. Feed dry matter intakes were less in the groups supplemented with probio-catalytic resulting in a better feed conversion ratio. The pH and concentration of ammonia of rumen fluid were not significantly different among treatments. While the acetic acid and propionic acid concentrations were not different among treatments, the butyric acid was significantly lower (P<0.05) in the groups received R3 and R4, whereas those received R2 and R3 was not significantly different than that of the control group. The molar proportion of volatile fatty acid components was within the normal values. Based on the results of the present experiment, it was concluded that addition of probio-catalytic supplement A at 0.5% was advantageous and it could be suggested to be included in the diet to improve the productive performance of sheep. Â Â Key Words: Probio-Catalytic Supplement, Productive Performance, Sheep